Controlling urea-N release using wood waste materials - Abd. Khalid, Nur Nabilah (2016)
This research attempts to perceive on the practicability of wood waste materials from oil palm frond (OPF) and rubber wood (RW) chips as the carrier for slow release fertilizer (SRF). RW residue was chosen in order to expand the usage of wood materials in the development of SRF, which previously utilize solid wood in the wood chips preparation for SRF production. Whereas the utilization of OPF can be explained by the abundant supply and high availability of this material which can be beneficial for environment and agricultural future in replacing synthetic material usage. Thus, basic anatomical characteristics and their relation to physical properties of oil palm frond and rubber wood as potential supporting material for slow release woodchips fertilizer was investigated, including microscopic structure study, quantitative fiber morphology and physical properties of both materials. This study revealed that OPF is found as more porous structure as well as having ability to absorb more water which is very favorable for nutrient deposition and release property of SRF. On the contrary, RW has thick cell wall which could be one of beneficial properties required for SRF carrier in order to hold and retain the impregnated nutrient in a longer time, thus make RW as possible material to be used in the production of wood waste chips SRF. Owing to aforementioned characteristics, it is expected that OPF and RW have their own advantageous, ability to be used as supporting material for SRF production in which they will facilitate the further process which is impregnation of nutrient fertilizer. The treatability of OPF and RW chips with urea was carried out using pressurized and non-pressurized impregnation processes, with three different levels of urea concentrations. Findings show that types of material, impregnation process and urea concentration did influence the treatability of oil palm frond and RW chips with urea solution. OPF was found to have higher weight percent gain (WPG) and nitrogen (N) retention compared to RW, and impregnation using pressurized method attained higher retention compared to non-pressurized method. Treatment with 15% urea concentration using pressurized process was found to be the most efficient treatment combination in the development of wood waste SRF. Further study on the nitrogen deposition into the impregnated woodchips fertilizer as well as the effects of cumulative nitrogen release pattern were also evaluated. The morphological changes of the impregnated woodchips was shown by VP-SEM, thus provide microscopic evidence of urea penetration into the microstructure of treated OPF and RW. By energy dispersive X-ray (EDX) analysis, the characteristic signals for N was detected clearly at 0.25 keV for OPF and 1.47 keV for RW. Release patterns of the nitrogen from impregnated woodchips were found slow and steady, particularly much slower in distilled water compared to soil solution. Other than that, the cumulative N release for OPF was found higher than RW in both leaching solution at the time interval of 768 h. Based on the results, the release pattern of both woodchips were similar to the conventional SRF, hence it is suggested that urea-impregnated woodchips fertilizer could function as a SRF that release nutrients gradually. Biodegradability test showed that treated chips decompose slower than untreated chips, whereas OPF chips have higher degradation rate than RW. In order to evaluate the effectiveness of the woodchips SRF on cultivation of crops, a field trial was conducted. Comparative effects of woodchips SRF, common NPK fertilizer, commercialized SRF and control (blank) were investigated on the growth performance and yield productivity of lady finger. Throughout the cultivation period, none of the plants were found dead. The findings also show that plant treated with urea-impregnated OPF has better vegetative growth in term of leaves and stem diameter, whereas application of urea-impregnated RW contribute to give higher fruit weight of lady fingers than OPF but did not give big influence in yield productivity of crops. Besides, significantly greater plant dry mass and N content were obtained with application of woodchips SRF. Therefore, it can be concluded that the urea-N release for slow release fertilizer can be controlled by utilization of wood waste materials from OPF and RW chips, which equally effective with the commercialized SRF in providing sufficient nutrients needed by the plant with less frequency of application than common compound fertilizer.